Median sternotomy approach for the repair of esophageal atresia: a case report - Hiroaki Fukuzawa; Mitsumasa Okamoto; Yudai Tsuruno; Ayako Maruo (Surgical Case Reports)
Abstract Background Repair of esophageal atresia is usually performed through the right thoracic cavity. However, when the upper pouch of the esophagus and tracheoesophageal fistula (TEF) is located in the thoracic inlet and completely on the left side of trachea, it is difficult to dissect and anastomose the esophagus through the right thoracic cavity. We present a case of esophageal atresia, with the esophageal upper pouch located high and completely on the left side of trachea, successfully repaired via the median sternotomy approach. Case presentation A male neonate with a birth weight of 1766 g was prematurely delivered via cesarean section at 34 weeks of gestation. Contrast-enhanced computed tomography (CT) showed that the upper pouch of the esophagus was located at the thoracic inlet and completely on the left side of the trachea; hence, a diagnosis of esophageal atresia was made. Moreover, a TEF was connected to the trachea at the level of the lower end of the upper esophageal pouch. An aberrant right subclavian artery and persistent left superior vena cava were also detected. Esophageal dissection and anastomosis were determined to be very difficult if approached from the right thoracic cavity. Therefore, we performed median sternotomy one day after the neonate was born. The upper pouch of the esophagus and TEF were easily dissected via the median sternotomy approach. Anastomosis of the esophagus was performed, with a good visual field, to the left of the trachea. The postoperative course was uneventful. Conclusions This is the first reported case of a median sternotomy approach for esophageal atresia. This technique may be useful when a right thoracic approach is difficult, especially if the esophageal upper pouch is located completely to the left of the trachea or if it is higher than the normal position.